2013
DOI: 10.1063/1.4799616
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio study of free standing TiO2 clusters: Stability and magnetism

Abstract: We report the structural behavior of nanoscale Titanium Dioxide (TiO 2 ) clusters as well as their magnetic properties by varying the cluster size with the help of ground state geometries. The clusters of atomic scale rutile (TiO 2 ) n , where n ¼ 1-11, have been considered and geometrically stabilized through the Density Functional Theory as implemented in Vienna ab-initio Simulation Package. It is being observed that as the size of cluster increases from n ¼ 2 to 11, the total energy decreases. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…In our study the particle sizes are found to be very small and it could not be derived from bulk. The structural and electronic properties of as synthesized hybrid nanomaterials could be significantly different than the bulk materials due to high surface to volume ratio as well as quantum confinement effect …”
Section: Resultsmentioning
confidence: 99%
“…In our study the particle sizes are found to be very small and it could not be derived from bulk. The structural and electronic properties of as synthesized hybrid nanomaterials could be significantly different than the bulk materials due to high surface to volume ratio as well as quantum confinement effect …”
Section: Resultsmentioning
confidence: 99%
“…Literature suggests cluster having even n are more stable than odd n clusters as former usually have covalent nature while the latter have ionic nature. 42 For computational simplicity, the semi-conductor (TiO 2 ) 4 was considered here. 32 Harmonic vibrational frequency calculations were performed and the positive frequency conrms the optimized structural minima.…”
Section: Computational Sectionmentioning
confidence: 99%
“…The study of TiO 2 ‐based clusters has been an attractive research area due to their wide range of applications . In order to make such investigations, first‐principles methods are primarily used to study the structural, optical, and vibrational properties of the clusters .…”
Section: Introductionmentioning
confidence: 99%